2013
DOI: 10.1093/heapol/czt095
|View full text |Cite
|
Sign up to set email alerts
|

What explains regulatory failure? Analysing the architecture of health care regulation in two Indian states

Abstract: Regulating health care is a pre-eminent policy challenge in many low- and middle-income countries (LMIC), particularly those with a strong private health sector. Yet, the regulatory approaches instituted in these countries have often been reported to be ineffective-India being exemplary. There is limited empirical research on the architecture and processes of health care regulation in LMIC that would explain these regulatory failures. We undertook a research study in two Indian states, with the aims of (1) map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 23 publications
1
95
1
Order By: Relevance
“…This may reflect continued patient demand for case management services across different outlet types as well as motivation among unauthorized providers to provide services to meet the demand. This may also reflect inadequate capacity of inspection and judiciary agencies, and a lack of resources to implement routine inspections as evidenced by other research [21, 22]. A review by Montagu and Goodman regarding the regulation of the private sector in developing countries has shown that regulatory approaches face persistent challenges [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect continued patient demand for case management services across different outlet types as well as motivation among unauthorized providers to provide services to meet the demand. This may also reflect inadequate capacity of inspection and judiciary agencies, and a lack of resources to implement routine inspections as evidenced by other research [21, 22]. A review by Montagu and Goodman regarding the regulation of the private sector in developing countries has shown that regulatory approaches face persistent challenges [23].…”
Section: Discussionmentioning
confidence: 99%
“…6 However, most of the private health-care providers are concentrated in urban India, providing secondary and tertiary care health-care services. The public health-care infrastructure in rural areas has been developed as a three-tier system based on the population norms and described below.…”
Section: Public Health-care Infrastructure In Indiamentioning
confidence: 99%
“…As emphasized by the GVG Consultancy Team, “Government entities deal separately with parts and parcels of the same subject contributing to lack of transparency and accountability, and in the case of a problem, no one is responsible.” Both legal and accountability issues have affected the effective implementation of regulations in Mongolia, along with the lack of technical and financial capacity and corruption. These are challenges shared by many other LMICs …”
Section: Discussionmentioning
confidence: 99%
“…These are challenges shared by many other LMICs. 17,19,[29][30][31][32] In governance, the dominance of the state in health regulation-as in Mongolia-is being increasingly criticized, as no single actor possesses the full range of knowledge required to solve such complex problems arising in such a pluralistic and complex health systems. 10,22,29,33 The disciplinary role of professional organizations, the empowerment of patients, the safeguarding of their rights to redress, and the increased involvement of civil society in designing and implementing health regulations are critical to advance governance in health regulations.…”
Section: Discussionmentioning
confidence: 99%